Pengaruh Metode Eksperimen Dengan Model Inkuiri Terbimbing Terhadap Kemampuan Berpikir Kreatif Peserta Didik Pada Pembelajaran Fisika - Nuning Rohmantika; Umi Pratiwi (Universitas PGRI Semarang, 2022)
Research has been carried out on the effect of using experimental methods using guided inquiry learning models on students' creative thinking skills in physics learning. The purpose of this study was to determine how much influence the experimental method combined with the guided inquiry learning model had on the creative thinking abilities of MA Al-Iman Bulus Purworejo students and to determine the effectiveness of learning physics through experimental methods on the subject of uniformly changing straight motion. Class X Mathematics and Natural Sciences became the population in this study, while the sample was class X MIPA 2 as many as 35 students. The technique used to collect data was in the form of a test method. Then the accumulated data is calculated using N-Gain and the data analysis used is the normality test and the t-test. The results of the N-Gain calculation are 0.44 and are included in the medium category. Normality test results obtained Asymp. Sig. (2-tailed) > 0.05. The results of data analysis through t-test obtained the results of Sig. (2-tailed) 0.000 < 0.05, so from this study it was concluded that there was an effect of the experimental method using the guided inquiry learning model on the creative thinking ability of students. Keywords: experimental method, guided inquiry, creative thinking ability